Schaum's Outline of International Economics: Theory and Problems - Salvatore D. (Dominick) (New York(State): The McGraw-Hill Companies, 1996)
This is the Fourth Edition of a book that has enjoyed gratifying market success and has been translated into Spanish, French, Italian, Portugues, Arabic, Indonesian, and Japanese. All of thee features that made the first three editions successful have been retained. Besides a thorough updating, the fourth edition includes important new theoretical developments and applications.
(NP(B/11138, (NP(B/14065-(NP(B/14066s
Keywords: trade -- growth -- markets